Intraspecific cytotypic variation and complicated genetic structure in the Phlox amabilis-P. woodhousei (Polemoniaceae) complex - Fehlberg, Shannon D.; Ferguson, Carolyn J. (My University, 2013)
• Premise of the study: Polyploidy is widely recognized as an important process in the evolution of plants, but less attention has been paid to the study of intraspecific polyploidy, including its prevalence, formation, taxonomic implications, and effect on genetic diversity, structure, and gene flow within and among individuals and populations. Here we studied intraspecific ploidy level variation in the Phlox amabilis – P. woodhousei complex to determine the amount and distribution of cytotypic and genetic variation present and measure the extent of gene flow among species, cytotypes, and populations. • Methods: Flow cytometry and microsatellite analyses were used to ascertain cytotypic variation, genetic diversity, and population structure within and among eight populations of P. amabilis and 10 populations of P. woodhousei from Arizona and New Mexico. • Key results: Our analyses support the recognition of P. amabilis and P. woodhousei as two distinct species. Both species exhibit cytotypic variation with geographically structured diploid, tetraploid, and hexaploid populations, and genetic analyses suggest a combination of auto- and allopolyploidy in their formation. Diploid, tetraploid, and most hexaploid populations within species share much of their genetic variation, while some hexaploid populations are genetically distinct. All populations maintain moderately high genetic diversity and connectivity, and genetic structure is strongly influenced by geography. • Conclusions: This study highlights the potential for complicated patterns of genetic variation relative to cytotypic variation and provides evidence for the role of cytotypic variation and geographic isolation in shaping diversity, differentiation, and potentially speciation in the P. amabilis – P. woodhousei complex.
Keywords: Allopolyploidy; Autopolyploidy; Cytotype; Flow cytometry; Gene flow; Microsatellites; Phlox; Polemoniaceae; Population genetics